2017
DOI: 10.3382/ps/pex178
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analytic study of organic acids as an alternative performance-enhancing feed additive to antibiotics for broiler chickens

Abstract: The effect of organic acids as an alternative to antibiotics on the performance of broiler chickens was evaluated by meta-analysis, identifying and quantifying the main factors that influence results. A total of 51,960 broilers from 121 articles published between 1991 and 2016 were used. Interactions of additives [non-supplemented group (control), organic acids, and growth promoter antibiotics] with microbial challenge (with or without inoculation of pathogenic microorganisms) were studied on performance varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
57
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 62 publications
2
57
0
6
Order By: Relevance
“…[1][2][3][4][5][6] In addition to all these uses,carboxylic acids serve as central building blocks for the preparation of derivatives like carboxylate salts,a nhydrides,e sters,n itriles, and amides. [1][2][3][4][5][6] In addition to all these uses,carboxylic acids serve as central building blocks for the preparation of derivatives like carboxylate salts,a nhydrides,e sters,n itriles, and amides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6] In addition to all these uses,carboxylic acids serve as central building blocks for the preparation of derivatives like carboxylate salts,a nhydrides,e sters,n itriles, and amides. [1][2][3][4][5][6] In addition to all these uses,carboxylic acids serve as central building blocks for the preparation of derivatives like carboxylate salts,a nhydrides,e sters,n itriles, and amides.…”
Section: Introductionmentioning
confidence: 99%
“…Carboxylic acids are of major importance in organic chemistry and industry.B ecause of the specific physical characteristics of this functional group (acidity,p olarity, surface properties) numerous applications exist for materials, pharmaceuticals,a grochemicals,c oatings,t he food industry, cosmetic ingredients,d isinfecting products,a nd other manufactured chemicals. [1][2][3][4][5][6] In addition to all these uses,carboxylic acids serve as central building blocks for the preparation of derivatives like carboxylate salts,a nhydrides,e sters,n itriles, and amides. [7][8][9][10][11][12][13] There is ac ontinuing interest in new applications of organic acids and their market is expected to grow by more than 5%from 2017 to 2022 to reach aprojected value of more than $11 billion by 2022.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies can be found in the literature establishing prediction equations for the energy values of a number of ingredients (NRC, 1994;Nascimento et al, 2009;Rostagno et al, 2017). However, the obtained results are only applicable to a group of feedstuffs, since one experiment alone reflects only the experimental conditions in which it was developed (Polycarpo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, due to the emergence of antimicrobial-resistant bacteria, society is pressing for a reduction in antibiotic administration by nding effective alternatives to control infectious diseases at farm level [21][22][23][24]. Some of these alternatives are feed additives (prebiotics, probiotics, symbiotics, organic acids, enzymes, phytogenics and metals), alternative medical treatments (antibacterial vaccines, immunomodulatory agents, antimicrobial peptides and bacteriophages) and, nally, different broiler growth systems [25][26][27][28][29][30][31]. Although the bene cial effects of many of these alternatives have been demonstrated in vitro, the general consensus is that the effect of these products depends on the farm, management and animal characteristics, such as the breed selected [19,23,32].…”
mentioning
confidence: 99%